Structural insights reveal the second base catalyst of isomaltose glucohydrolase. (30th October 2021) - Tagami, Takayoshi; Chen, Minghao; Furunaga, Yuta; Kikuchi, Asako; Sadahiro, Juri; Lang, Weeranuch; Okuyama, Masayuki; Tanaka, Yoshikazu; Iwasaki, Tomohito; Yao, Min; Kimura, Atsuo
Abstract : Glycoside hydrolase family 15 (GH15) inverting enzymes contain two glutamate residues functioning as a general acid catalyst and a general base catalyst, for isomaltose glucohydrolase (IGHase), Glu178 and Glu335, respectively. Generally, a two‐catalytic residue‐mediated reaction exhibits a typical bell‐shaped pH–activity curve. However, IGHase is found to display atypical non‐bell‐shaped pH‐ k cat and pH‐ k cat / K m profiles, theoretically better‐fitted to a three‐catalytic residue‐associated pH–activity curve. We determined the crystal structure of IGHase by the single‐wavelength anomalous dispersion method using sulfur atoms and the cocrystal structure of a catalytic base mutant E335A with isomaltose. Although the activity of E335A was undetectable, the electron density observed in its active site pocket did not correspond to an isomaltose but a glycerol and a β‐glucose, cryoprotectant, and hydrolysis product. Our structural and biochemical analyses of several mutant enzymes suggest that Tyr48 acts as a second catalytic base catalyst. Y48F mutant displayed almost equivalent specific activity to a catalytic acid mutant E178A. Tyr48, highly conserved in all GH15 members, is fixed by another Tyr residue in many GH15 enzymes; the latter Tyr is replaced by Phe290 in IGHase. The pH profile of F290Y mutant changed to a bell‐shaped curve, suggesting that Phe290 is a key residue distinguishing Tyr48 of IGHase from other GH15 members. Furthermore, F290Y is found to accelerate the condensation of isomaltose from glucose by modifying a hydrogen‐bonding network between Tyr290‐Tyr48‐Glu335. The present study indicates that the atypical Phe290 makes Tyr48 of IGHase unique among GH15 enzymes. Abstract : Enzymes having two catalytic residues exhibit a typical bell‐shaped pH–activity curve. However, isomaltose glucohydrolase displayed atypical non‐bell‐shaped pH‐ k cat and pH‐ k cat / K m profiles, indicating this enzyme possesses three catalytic residues. This report provides structural and kinetical evidence that unusual Phe290 allows Tyr48 to act as a second catalytic base.